SECONDARY SUCCESSION IN ABANDONED CROP FALLOWS: A REVIEW - Pathak, Hom N (International Journal of Environment, 2015)
The succession in areas once vegetated before the disturbance to a forest as climax community is called secondary succession. Secondary succession is influenced by soil type and the vegetation that invades the community. During the literature survey we found that the cropping areas are abandoned in different parts of the world and the fallows left are under secondary succession. There the socio-economy of the people has been found to affect the succession. Species diversity, species richness, rate of replacement and the soil type etc. have been studied by succession researchers. Succession study has also been carried out by using the tools like remote sensing, geographical information system etc.International Journal of Environment Volume-4, Issue-3, June-August 2015Page: 166-176